The creativity and music analysis of Li Xiangjing’s Nanyin Poetry and Painting / Wang Xiaolu - Wang, Xiaolu (2019)
In nowadays China, traditional music tends to develop by hybridising the Western and modern musical elements to meet the world trend of globalisation. Nanyin music, as a genre of traditional southern Chinese music, has fused with various Western musical elements to a new form in the modern age. The modern Nanyin works show the cross-cultural phenomenon. There are many modern Nanyin music works. The forms of new Nanyin are varied in symphony, violin concerto, overture, the combination of Chinese and the Western strings, but basically rare in the chamber form. The music Nanyin Poetry and Painting composed by Li Xiangjing in 2013 is the one in the chamber form. Compared to the other musical forms, the chamber form is more consistent with the traditional Nanyin style since traditional Nanyin is a chamber music. This paper aims to have an in-depth analysis of the modern Nanyin work of Nanyin Poetry and Painting composed by Li Xiangjing; to provide resources to music scholars and performers for a deeper musical understanding of how the traditional Nanyin elements hybridised with the Western compositional techniques by the composer; to explore the composer’s musical intention and consideration during composition period; and to the music audience, a better musical appreciation of this work.